A Modified Theoretical Model to Accurately Account for Interfacial Roughness in Predicting the Interfacial Thermal Conductance - Zhang, Yingying; Ma, Dengke; Zang, Yi; Wang, Xiaojia; Yang, Nuo (Frontiers in Energy Research, 2018)
The acoustic mismatch model and the diffuse mismatch model (DMM) have been widely used to predict the thermal interface conductance. However, the acoustic mismatch model and the DMM are based on the hypothesis of a perfectly smooth interface and a completely disordered interface respectively. Here, we present a new modified model, named as the mixed mismatch model, which considers the roughness/bonding at the interface. By taking partially specular and partially diffuse transmission into account, the mixed mismatch model (MMM) can predict the thermal interface conductance with arbitrary roughness. The proportions of specular and diffuse transmission are determined by the interface roughness which is described by the interfacial density of states. We show that the predicted results of the MMM match well with the values of molecular dynamics simulation and experimental data.